The impact of institutional quality on human development in Sub-Sahara African countries - Ejuvbekpokpo, Stephen Akpo (2016)
Despite the abundant research on institutional quality and development, little has been done to examine the impact of institutional quality on human development in Sub-Sahara African (SSA) countries. Many institutions in the SSA are problematic because of weak rules of law, high level of corruption, poor bureaucratic quality and low property rights which have resulted in low level of human development, standard of living, educational attainment and life expectancy. Institutions and economic transformations through human development have become the central focus of the development agenda in developing countries.The objective of this study evaluates the relationship between institutional quality and human development in SSA countries from 2005 to 2013. The study used secondary data which were sourced from World Bank governance indicators and Transparency International. The empirical analysis used both static and dynamic panel data. The study aggregated and disaggregated human development indicator into three components namely; standard of living, educational attainment and life expectancy. The SSA countries are divided into low income and lower middle-income countries. The empirical results of fixed effects model, random effects model and the General Method of Moments (GMM) produced similar outcomes. The results suggest that institutional quality contributes to the low level of human development of SSA countries. In addition, most of the investigated countries exhibits mixed performance in terms of the institutional quality and human development. Nevertheless, the results signify that institutional quality plays vital role in human development in the SSA countries. Consequently, the study recommends policies such as economic and political reforms to strengthen the institutional quality, to fight corruption, to enforce strong law for effective regulations and implementation in the region. Finally, human development capabilities need urgent attention to improve the standard of living of the people and to attain their yearnings and aspirations in life.